FORMULASI CREAMBATH DENGAN VARIASI KONSENTRASI SARI BONGGOL PISANG AMBON (Musa acuminata Colla) - Teti Indrawati; Nabhilla Sofia (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Ambon banana (Musa acuminata Colla) humps contain anthraquinone compounds that effectives This research aims to take advantage of the hump to be confectionary cream bath as hair growth. Water extracts of Ambon banana humps were blended and filtered, and then, this water extracts of Ambon banana was made into cream bath using concentration of 8%, 10%, and 12%. The method that is used to make cream bath is dissolution and mixing methods at a temperature of 75oC–80oC and the water extract was add at 40oC. These cream bath products weres evaluated by organoleptic, homogeneity, emulsion type, pH, spreading ability, viscosity and flow character. All formula cream bath preparations had white to ivory white, odourless bananas, emulsion type o/w, homogenized, pH 6.05 to 6.38, spreading ability 4862.05 mm2-3672.67 mm2, has a viscosity of 12000 cps-145000 cps, and showed the flow properties pseudo-plastic thixotropic.